A rating-based conjoint analysis on the drivers of choice for plant-based meat alternatives (PBMAS) in Metro Manila - De Leon, Jonas Voltaire G.; Gozales, Benjamin A. (Quezon City University of the Philippines Diliman, 2023)
The demand for plant-based meat alternatives (PBMAs) has been increasing in popularity in the Philippines. A better knowledge of the drivers of choice that motivate Filipino PBMA purchasers and consumers is necessary to increase its marketability in the country. The study aims to determine which PBMA product attributes Filipinos deem the most and least essential and identify which product combination would generate the highest utility. Moreover, it aims to compare three consumer groups (A: purchasers and consumers of both PBMAs and animal-based meats (ABMs); B: purchasers and consumers of PBMAs only; and C: purchasers of PBMAs only) and on the level of their agreement towards evolving driver statements and recommend strategies to promote PBMAs in the Philippine setting effectively. One hundred fifty respondents were pooled based on their consumer group. Results showed that the sensory attribute and the price level were the most and least important attributes, respectively. The preferred combination for a PBMA is a focus on its taste, in cubes form, familiar and traditional, culturally relevant in today’s society, labeled with ‘Rich in Nutrients’, and range costs Php 150-200 per 100 grams using Rating-based Conjoint Analysis (RCA). Kruskal-Wallis H Test showed no significant differences in the level of agreement between the three consumer groups (p > 0.05). The individual responses and theoretical research suggest that PBMAs be as familiar and traditional as possible and potentially maintained at a price range of Php 100 to 150 per 100 grams or lesser (less than Php 100 to 150 per 100 grams) based on the upward trend of the conjoint results. Market strategies such as sensory tests, promotions, and discounts are recommended.
Thesis
Includes bibliographical references (pages 61-88)
Keywords: Meat substitutes -- Philippines; Food preferences -- Philippines